Intensified process based on reactive distillation for Triacetin production via glycerol esterification with acetic acid - Nattawat Petchsoongsakul; Kanokwan Ngaosuwan; Worapon Kiatkittipong; Doonyapong Wongsawaeng; Weerinda Mens; Santi Chuetor; Pongtorn Charoensuppanimit; Armando T. Quitain; Tetsuya Kida; Suttichai Assabumrungrat (Scientific Reports)
Abstract This study investigated the valorization of glycerol through triacetin (TA) production via glycerol esterification with acetic acid using reactive distillation (RD). The conventional TA production typically involved multiple unit operations, leading to process complexity and high costs. A simplified TA production process based on the appropriate design for RD was developed. The simulation results, validated by a robust kinetic model, demonstrated the high accuracy to predict glycerol conversion and TA purity. The optimized RD required only 32 theoretical stages using an acetic acid to glycerol feed molar ratio of 3:1, glycerol feed at the 2nd stage, acetic acid feed at the 31st stage, a reflux ratio of 7, and a bottom to feed ratio of 0.25 under column pressure of 0.7 bar without an entrainer. This configuration achieved the remarkable performance, with a 99.20% glycerol conversion, 99.41% TA selectivity, and 99.00% TA purity. The number of unit operations of RD process was reduced to 50%, leading to acquiring only 79.16% of the capital cost as compared to the conventional method. This finding highlights the economic advantage of the RD process, offering a sustainable, cost-effective, and scalable alternative for large-scale TA production.